Eksistensi dan Makna Simbolik Kesenian Bantengan di Malang - Rohmah, Siti Afifatur (Universitas Negeri Padang, 2025)
Bantengan Art is a traditional performance art originating from Malang, East Java. This art form combines dance, music, poetry, and attractions that depict the battle between good and evil through the symbol of the bull. In addition to serving as a ritual to ward off misfortune and purify the village, this art also functions as entertainment and as a means of preserving the local cultural traditions of Malang. This study aims to describe the existence and symbolic meaning of Bantengan Art in Malang. The research is qualitative in nature. The approach used to address the issues employs Parson’s theory of existence and Mead’s theory of symbolic interactionism. The data consist of informant statements and Bantengan performances. Data collection techniques include interviews and field observations during performances. The results show that Bantengan Art not only survives amid the current of modernization but also adapts through innovations in music, costumes, and performance media. Bantengan Art continues to hold strong social, spiritual, and cultural functions and serves as a collective space to strengthen values of solidarity, local identity, and the preservation of traditional cultural heritage in Malang. Symbolic elements such as the bull figure, trance performances, and traditional musical accompaniment are interpreted as representations of strength, courage, and spiritual communication between humans and their ancestors. Thus, Bantengan Art is not merely entertainment, but a cultural legacy rich in meaning, a representation of cultural identity, and a medium to strengthen social bonds within the Malang community. Keywords: Bantengan art, existence, symbolic meaning, tradition, local culture Malang